1980
DOI: 10.1038/clpt.1980.92
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urine changes after smoking different brands of cigarettes

Abstract: Concentrations of nicotine, cotinine, and carboxyhemoglobin (COHb) were measured in the plasma of subjects who smoked 1 cigarette of each of 10 different brands and then smoked 1 brand for 2 wk. There were higher COHb levels in smokers of low CO-yield cigarettes, whereas the rise in nicotine after 1 cigarette of each of the different brands was related to its nicotine content. Assay of urinary and plasma cotinine levels in smokers smoking brands with different nicotine content showed that smokers adjusted thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 10 publications
3
30
0
Order By: Relevance
“…With nicotine concentrations the CPD correlations are 0.38 for pre-smoking measures [17] and range between -0.33 and +0.10 for post-smoking values (median ~0.00) [10,12,25,28], and with cotinine concentrations the correlations are about 0.40 (range 0.34-0.54) [3,4,16,17,24]. The correlations obtained in the present study are consistent with those reported in the literature, except for post-smoking nicotine concentrations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…With nicotine concentrations the CPD correlations are 0.38 for pre-smoking measures [17] and range between -0.33 and +0.10 for post-smoking values (median ~0.00) [10,12,25,28], and with cotinine concentrations the correlations are about 0.40 (range 0.34-0.54) [3,4,16,17,24]. The correlations obtained in the present study are consistent with those reported in the literature, except for post-smoking nicotine concentrations.…”
Section: Discussionsupporting
confidence: 82%
“…CPD correlations with CO concentrations range between 0.11 and 0.73 (median=0.35) [16,19,24,26,28]. With nicotine concentrations the CPD correlations are 0.38 for pre-smoking measures [17] and range between -0.33 and +0.10 for post-smoking values (median ~0.00) [10,12,25,28], and with cotinine concentrations the correlations are about 0.40 (range 0.34-0.54) [3,4,16,17,24].…”
Section: Discussionmentioning
confidence: 96%
“…The health implications of this change have provoked discussion and confusion among health researchers, policy makers, and smokers.2 The validity of machine-determined values as predictors of what is actually smoked and even the logic behind the popular low-tar, lownicotine approach to safer cigarettes have been challenged.' [3][4][5][6][7][8][9][10] A particular criticism of machine-determined values of nicotine delivery is that smokers may compensate for reduced deliveries by taking more or larger puffs. The cigarettes used in most studies, however, have varied not only in nicotine content but in tar and carbon monoxide yields, flavouring agents, filter types, and size.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute and dispersed values of cotinine reported are very different referring to the measurement methods and detection media. Plasma concentrations between 100 and 200 ng/ml in smokers were seen by Hill and Marquardt [24] and Gritz et al [25] .…”
Section: Cotinine In Serummentioning
confidence: 82%